Acanthosis Nigricans and Its Response to Metformin. Issue 5 (30th July 2017) - Giri, Dinesh; Alsaffar, Hussain; Ramakrishnan, Renuka
Abstract: Acanthosis nigricans (AN) is the most common cutaneous manifestation of insulin resistance (IR) and is commonly seen in non‐Caucasian populations. Variable benefits of metformin in the treatment of AN have been reported in the literature. We report an adolescent Caucasian boy with IR and extensive AN who showed complete resolution of AN after 2 years of metformin, despite persistence of IR.